Pemberdayaan Santri melalui Edukasi Personal Hygiene dan Perilaku Hidup Bersih dan Sehat (PHBS) sebagai Upaya Pencegahan Scabies di Pondok Pesantren Bani Asnawi Pandeglang - Heny Sasmita; Erma Noor Wahyuningsih; Devi Oktaviani; Alysha Naswa Fierdaoest; Adzwa Subhiyya; Indy Rhaya Ardelia; Ine Risma Yanto; Rizki Fajarul Maududi; Ilham Wahid; M Azril Khperul Rijal; Ucu Wandi Somantri (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Scabies is a contagious skin disease that remains a significant public health problem in Islamic boarding schools due to overcrowded living conditions, shared personal facilities, and inadequate implementation of Personal Hygiene and Clean and Healthy Living Behavior (PHBS). This community service program aimed to improve students' knowledge and awareness regarding scabies prevention through empowerment-based health education. The program was conducted at Bani Asnawi Islamic Boarding School, Pakis Hamlet, Sukalangu Village, Saketi District, Pandeglang Regency, involving 30 students consisting of 17 female and 13 male students. Educational activities were delivered using PowerPoint presentations, posters, and standing banners, followed by knowledge assessment through pre-test and post-test questionnaires. The results demonstrated an improvement in students' knowledge regarding the causes, modes of transmission, signs and symptoms, and preventive measures of scabies after the educational intervention. Participants also showed better understanding of the importance of maintaining Personal Hygiene, avoiding the sharing of personal belongings, and preserving environmental cleanliness within the boarding school. Empowerment-based health education proved effective in enhancing students' health literacy and is expected to encourage sustainable clean and healthy living behaviors as promotive and preventive strategies to reduce the risk of scabies transmission in Islamic boarding school settings.